2019
DOI: 10.1252/jcej.18we219
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dechlorination of Polyvinyl Chloride by Microwave Irradiation

Abstract: The present study investigates microwave irradiation to develop the recycling technology of any kind of plastic waste containing organic chlorine, dechlorination. Polyvinyl chloride (PVC) was used as a typical organic chlorine. Under constant sample temperature, the PVC dechlorination properties were compared between microwave irradiation and conventional heating. It was clari ed that microwave irradiation induced much faster dechlorination than conventional heating. It was also found that the dechlorination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Dehalogenation of the waste fractions can be performed prior to the pyrolysis. Techniques include thermal dehalogenation which can be performed as a stand-alone process (Bockhorn et al, 1999, Yoshioka et al, 2000, Ma et al, 2004, Sakata et al, 1998, or in combination with extrusive feeding (Saito and Narita, 2001, Fukushima et al, 2010, Okuwaki et al, 2006, Kobayashi et al, 2019.…”
Section: Feedstock Characterizationmentioning
confidence: 99%
“…Dehalogenation of the waste fractions can be performed prior to the pyrolysis. Techniques include thermal dehalogenation which can be performed as a stand-alone process (Bockhorn et al, 1999, Yoshioka et al, 2000, Ma et al, 2004, Sakata et al, 1998, or in combination with extrusive feeding (Saito and Narita, 2001, Fukushima et al, 2010, Okuwaki et al, 2006, Kobayashi et al, 2019.…”
Section: Feedstock Characterizationmentioning
confidence: 99%
“…Next to thermal pre-treatment methods, selective dechlorination of PVC by microwave irradiation was studied by a number of authors [59][60][61][62]. While polyolefins have very low dielectric constants and are therefore essentially transparent to microwaves, the C-Cl bond in PVC is highly polar and responsive to microwave irradiation [59,63]. It was reported that microwave irradiation reduced the dechlorination temperature of PVC to 200-210…”
Section: Stand-alone Dehalogenation Techniquesmentioning
confidence: 99%